2018
DOI: 10.1111/cea.13103
|View full text |Cite
|
Sign up to set email alerts
|

The absence of serum IgE antibodies indicates non‐type 2 disease in young asthmatics

Abstract: Clinically relevant elevation of type 2 biomarkers was seen in young asthmatics with IgE antibodies <0.35 kU /L, but not those with IgE < 0.10 kU /L. It seems possible to define non-type 2 asthma through sensitive IgE-antibody measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
3
5
0
1
Order By: Relevance
“…The present results further strengthen the earlier observations, since we managed to objectively confirm the presence of airway disease including airway hyper-responsiveness and reduced FEV 1 /FVC ratio. We have recently reported data showing weak type 2 inflammatory signals in young asthmatics with IgE antibody concentrations below 0.35 kU A /L, suggesting a cut-off of 0.10 kU A /L for ruling out the presence of such inflammation [4]. In the present study, 58% of the subjects that reported hypersensitivity to cow’s milk had undetectable IgE antibody concentrations (< 0.10 kU A /L).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The present results further strengthen the earlier observations, since we managed to objectively confirm the presence of airway disease including airway hyper-responsiveness and reduced FEV 1 /FVC ratio. We have recently reported data showing weak type 2 inflammatory signals in young asthmatics with IgE antibody concentrations below 0.35 kU A /L, suggesting a cut-off of 0.10 kU A /L for ruling out the presence of such inflammation [4]. In the present study, 58% of the subjects that reported hypersensitivity to cow’s milk had undetectable IgE antibody concentrations (< 0.10 kU A /L).…”
Section: Discussionsupporting
confidence: 43%
“…It is well‐known that elevated fraction of exhaled nitric oxide (FeNO) and blood eosinophil (B‐Eos) count are clinically useful type 2 biomarkers in asthma, and their simultaneous elevation has shown independent and additive predictive value for asthma morbidity [2, 3 ]. We have recently reported the persistence of clinically relevant type 2 inflammatory signals in young asthmatics with IgE antibody concentrations below 0.35 kU A /L, and we have suggested a cut‐off of 0.10 kU A /L for ruling out type 2 inflammation [4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important observation derived from the stratification into different sIgE groups was that a significant reduction in lung function over time was seen in the elevated and detectable sIgE groups but was absent in the group with undetectable sIgE. This finding is supported by our recent study, highlighting the presence of clinically significant type‐2 inflammation in patients with low but detectable sIgE levels (0.10–0.34 kU A /L) but not in patients with undetectable sIgE 9 . The cut‐off of 0.10 kU A /L for ruling out IgE sensitization used in this study contrasts with clinical routine where a higher cut‐off level of 0.35 kU A /L or a wheal diameter for skin prick test greater than 3 mm is commonly used for defining atopy.…”
Section: Discussionsupporting
confidence: 71%
“…The incidence of nonallergic asthma remains significantly higher in women than men throughout their reproductive years (>20 years old), with both higher incidence and prevalence of nonallergic asthma observed in the later reproductive years (>35 years old) 116 . Nonallergic asthma in young adults is also significantly increased in women and is associated with decreased allergen sensitization and decreased T2 markers consistent with T2-low asthma 117 . Older age, decreased allergen sensitization, and absence of allergic rhinitis are also associated with more severe asthma 118 .…”
Section: Discussionmentioning
confidence: 99%